2002
DOI: 10.1021/es001774i
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Studies of the Effects of Selenate and Selenite on Cobalt Sorption to γ-Al2O3

Abstract: The fate and transport of toxic metal ions and radionuclides in the environment is often controlled by sorption reactions. The extent of sorption of divalent metal cations is controlled by a number of factors including the presence of cosorbing or complexing ligands. To study the impact of anion cosorption on metal cation sorption behavior, Co(II) sorption to gamma-Al2O3 in the presence of selenium oxyanions was investigated. To aid in the interpretation of macroscopic sorption results, X-ray absorption spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
14
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 27 publications
3
14
0
Order By: Relevance
“…(2) Se (IV) sorption is not significantly affected by changes in pH or ionic strength; and (3) sorption occurs largely due to the formation of surface complexes (Davis and Misra 1997;Wijnja and Schulthess 2000;Su and Suarez 2000;Boyle-Wight et al 2002;Hayes et al 1987;Balistrieri and Chao 1990;Parida et al 1997). X-ray absorption spectroscopy (XAS) studies confirm that Se (IV) can form strong inner and/or outer-sphere complexes with metal oxides depending on pH, while Se (VI) complexes with metal oxides are relatively weak.…”
Section: Introductionmentioning
confidence: 99%
“…(2) Se (IV) sorption is not significantly affected by changes in pH or ionic strength; and (3) sorption occurs largely due to the formation of surface complexes (Davis and Misra 1997;Wijnja and Schulthess 2000;Su and Suarez 2000;Boyle-Wight et al 2002;Hayes et al 1987;Balistrieri and Chao 1990;Parida et al 1997). X-ray absorption spectroscopy (XAS) studies confirm that Se (IV) can form strong inner and/or outer-sphere complexes with metal oxides depending on pH, while Se (VI) complexes with metal oxides are relatively weak.…”
Section: Introductionmentioning
confidence: 99%
“…Inner-sphere complexation as well as induced surface precipitation and polymerization have been reported in the interaction of metals with alumina surfaces [9][10][11][26][27][28][29]. Operative retention mechanisms depend on the specific mineral phase and trace ele- 4 Þ is the oxyanion of hexavalent Cr.…”
Section: Introductionmentioning
confidence: 99%
“…On both Al substrates, selenite was found to form mononuclear complexes with three O atoms in the first coordination shell; although no Al scattering could be positively identified in the EXAFS data of adsorbed selenite, the independence of selenite adsorption on ionic strength suggested inner-sphere complexation of selenite on these sorbents. Boyle-Wight et al [27,28] used EXAFS to study selenate and selenite speciation in c-Al 2 O 3 suspensions in the presence and absence of Co(II). These authors found that selenate did not affect Co(II) sorption by c-Al 2 O 3 , whereas selenite enhanced Co(II) sorption due to formation of ternary Co(II)-selenite complexes and/or the precipitation of selenite/Co(II) phases; the coordination of selenate and selenite to the c-Al 2 O 3 surface in binary selenite-or selenatec-Al 2 O 3 systems was not addressed in this study.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that different aluminum oxide minerals will form a bayerite-type surface layer upon hydration [16] and therefore the effect of mineral structures upon surface chemistry may not be as significant with aluminum oxides. Additionally, the vast majority of aluminum oxides in soils are of the Al(OH) 3 form, as either gibbsite or amorphous coatings on other soil surfaces.…”
Section: Introductionmentioning
confidence: 99%